2018
DOI: 10.1039/c8ta00221e
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature solid state dual-ion batteries based on gel electrolytes

Abstract: The solid-state dual-ion battery delivers a high reversible capacity of 80 mA h g−1, with long-term cycling stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…53,56−66 It is further observed in Table 2 that the Li-ion battery fabricated with ionogel-3 shows a high specific discharge capacity comparable to or even better than those of batteries reported earlier. 53,56−66 Also, the dual-ion battery shows higher capacity and average discharge voltage (≥4.5 V) than those reported earlier, 13,66 indicating a high energy density at room temperature. It may be noted that only a few studies are available for the dual-ion battery.…”
Section: Resultsmentioning
confidence: 86%
“…53,56−66 It is further observed in Table 2 that the Li-ion battery fabricated with ionogel-3 shows a high specific discharge capacity comparable to or even better than those of batteries reported earlier. 53,56−66 Also, the dual-ion battery shows higher capacity and average discharge voltage (≥4.5 V) than those reported earlier, 13,66 indicating a high energy density at room temperature. It may be noted that only a few studies are available for the dual-ion battery.…”
Section: Resultsmentioning
confidence: 86%
“…have proposed a GPE, PVDF‐HFP/SiO 2 soaked by LiPF 6 /EMC+3 wt.% VC, for a graphite cathode. The graphite cathode displayed a high reversible capacity of 80 mAh g −1 at 200 mA g −1 and an excellent cycling performance with a capacity retention of 82.0 % over 1,000 cycles . Chen et al.…”
Section: Gel Polymer Electrolytementioning
confidence: 99%
“…The graphite cathode displayed a high reversible capacity of 80 mAh g À 1 at 200 mA g À 1 and an excellent cycling performance with a capacity retention of 82.0 % over 1,000 cycles. [158] Chen et al reported a flexible dual-ion battery based on a PVDF-HFP/PEO/ GO GPE (PEO: poly(ethylene oxide); GO: graphene oxide) soaked with 4 M LiPF 6 /EMC + 2 % VC (Figure 11a). [159] The cell exhibited a high discharge capacity of~100 mAh g À 1 at 500 mA g À 1 with an average voltage of 4.0 V and outstanding cycling stability, with a capacity retention of 92 % after 2,000 cycles (Figure 11b).…”
Section: Gel Polymer Electrolytementioning
confidence: 99%
“…Moreover, good flexibility and thermal stability (up to 90 °C) were also achieved for this DIB. Except for GO, other inorganic fillers such as Al 2 O 3 [ 80 ] or SiO 2 [ 75 ] added in PVDF–HFP to form porous GPEs after immersing organic electrolytes were also reported for DIBs, which displayed high working voltage and reversible capacity, good rate performance, and excellent cycling stability.…”
Section: Electrolytesmentioning
confidence: 99%